2017
DOI: 10.2147/ndt.s126979
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical study of D-serine metabolism among schizophrenia patients

Abstract: BackgroundSchizophrenia is a typical N-methyl-d-aspartate receptor (NMDA-R) hypofunction disorder. Decreased d-serine (d-Ser) levels in the periphery occur in schizophrenia and may reflect decreased availability of d-Ser to activate NMDA-R in the brain.ObjectiveThe objective of this study was to investigate the role of d-Ser metabolism in the pathogenesis of schizophrenia via biochemical assays and correlates, the serum level of d-Ser, d-serine racemase (SR) (responsible for its formation from l-serine [l-Ser]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
(45 reference statements)
0
17
0
1
Order By: Relevance
“…Thus, it has been widely studied in schizophrenia patients. It was indicated that serum d-serine level was lower in patients with schizophrenia when compared to healthy control (Cho, Na, Cho, & Kang, 2016;El-Tallawy et al, 2017). d-amino acid oxidase (DAAO), the enzyme responsible for catabolism of the d-serine, was also found to be higher in schizophrenia patients when compared control group (El-Tallawy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been widely studied in schizophrenia patients. It was indicated that serum d-serine level was lower in patients with schizophrenia when compared to healthy control (Cho, Na, Cho, & Kang, 2016;El-Tallawy et al, 2017). d-amino acid oxidase (DAAO), the enzyme responsible for catabolism of the d-serine, was also found to be higher in schizophrenia patients when compared control group (El-Tallawy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that D-serine protects against schizophrenia, and that its loss reduces activation of NMDA receptors, bringing about schizophrenic symptoms [ 45 , 46 , 113 , 114 , 115 , 116 ]. Indeed, a number of studies have found that giving schizophrenic patients high doses of D-serine mitigates negative symptoms of schizophrenia [ 45 , 117 , 118 , 119 ].…”
Section: Nmda Receptor Agonists or Co-agonistsmentioning
confidence: 99%
“…Indeed, a number of studies have found that giving schizophrenic patients high doses of D-serine mitigates negative symptoms of schizophrenia [ 45 , 117 , 118 , 119 ]. This is important because it has recently been shown that D-serine levels are significantly lower in humans suffering from Schizophrenia, probably caused by blunted expression of serine racemase and overexpression of DAAO [ 114 ]. D-Serine plays a role in the onset of Alzheimer’s Disease and dementias [ 33 , 43 , 47 , 120 ].…”
Section: Nmda Receptor Agonists or Co-agonistsmentioning
confidence: 99%
“…Ïîìèìî ýòîãî, îáíàðóaeèâàþòñÿ çíà÷èòåëüíî áîëåå âûñîêèå óðîâíè àëàíèíà, ãëèöèíà, ëåéöèíà è ôåíèëàëàíèíà â ñïèííîìîçãîâîé aeèäêîñòè ïàöèåíòîâ ñ øèçîôðåíèåé ïî ñðàâíåíèþ ñ çäîðîâûìè ëþäüìè [31]. Ïîëîaeåíèå, ÷òî íàðóøåííûé ìåòàáîëèçì D-ñåðèíà ìîaeåò ÿâëÿòüñÿ ïðåäèêòîðîì øèçîôðåíèè, íàøëî ïîäòâåðaeäåíèå è â ïîñëåäíèõ ñòàòüÿõ [32,33]. S. Saleem ñ ñîàâò.…”
Section: изучение роли аминокислот и ацилкарнитинов в патогенезе шизоunclassified